Single-vesicle intensity and colocalization fluorescence microscopy to study lipid vesicle fusion, fission, and lipid exchange - Andersson, Alexandra; Fornasier, Marco; Makasewicz, Katarzyna; Pálmadóttir, Tinna; Linse, Sara; Sparr, Emma; Jönsson, Peter (Frontiers in Molecular Neuroscience, 2022)
Interactions of lipid vesicles play important roles in a large variety of functions and disfunctions in the human body. Vital for several biochemical functions is the interaction between monomeric proteins and lipid membranes and the induced phenomena, such as fusion between vesicles and cell membranes, lipid exchange between the membranes or vesicle fission. Identification of single events, and their frequency of occurrence would provide valuable information about protein-lipid interactions in both healthy and degenerative pathways. In this work, we present a single vesicle intensity and colocalization fluorescence microscopy assay with a custom-written MATLAB analysis program. The assay can be used to study lipid exchange as well as vesicle fusion and fission between two vesicle populations labelled with different fluorescent dyes. Vesicles from the two populations are first mixed and docked to a glass surface. The sample is then simultaneously imaged using two separate wavelength channels monitoring intensity changes and colocalization of vesicles from the two populations. The monomeric pre-synaptic protein α-synuclein (α-syn) and small unilamellar vesicles consisting of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), 1,2-dioleoyl-sn-glycero-3-phospho-L-serine, (DOPS) and monosialotetrahexosylganglioside (GM1) were used as a model system to evaluate the method. From our analysis, neither α-syn induced fusion nor lipid exchange was observed for vesicles consisting of DOPC:DOPS (7:3). However, including 10% GM1 in the vesicles resulted in a 91% increase of the number of vesicles within 10 min, combined with a 57% decrease in the average fluorescence intensity per vesicle, indicating that approximately half of the vesicles underwent fission. The method facilitates the study of lipid vesicle fusion, fission and lipid exchange under controlled conditions, and also allows these events to be studied for systems with more complex composition including exosomes and lipid-based drug carriers, to enable a better understanding of their physicochemical properties.